A metamodeling approach for the simulation of energy and media demand for the brewing industry. Issue 2 (23rd March 2021) - Bär, Raik M.; Voigt, Tobias
Abstract: Due to economic, social and technical trends, as well as rising energy costs, the food and beverage industry is challenged to work energy‐efficiently. Small and medium‐sized enterprises in particular lack of both time and knowledge to identify and implement suitable energy efficiency measures. With the help of simulation, decision‐makers can pursue numerous approaches and make well‐founded decisions. A metamodel based on four modeling pillars (physical‐, process‐, article/recipe‐, and production plan model) for an entire production system concerning the forecast of energy and media consumption is presented. The metamodel is implemented in a user‐friendly modeling tool, which enables a simple hybrid modeling without prequalification of the user. Subsequently, a standardized data exchange file, as basis for a simulation model, is generated. For validation, various use cases were modeled and the tool was validated using a systematic test. In addition, two simulation studies were performed to show that the presented approach provides the opportunity to create a holistic model in terms of forecasting energy and media consumption.